Precast Prestressed Concrete Truss-Girder for Roof Applications. (11th December 2014) - Samir, Peter; Morcous, George
Abstract : Steel trusses are the most popular system for supporting long-span roofs in commercial buildings, such as warehouses and aircraft hangars. There are several advantages of steel trusses, such as lightweight, ease of handling and erection, and geometric flexibility. However, they have some drawbacks, such as high material and maintenance cost, and low fire resistance. In this paper, a precast concrete truss is proposed as an alternative to steel trusses for spans up to 48 m (160 ft) without intermediate supports. The proposed design is easy to produce and has lower construction and maintenance costs than steel trusses. The truss consists of two segments that are formed using standard bridge girder forms with block-outs in the web which result in having diagonals and vertical members and reduces girder weight. The two segments are then connected using a wet joint and post-tensioned longitudinally to form a crowned truss. The proposed design optimizes the truss-girder member locations, cross-sections, and material use. A 9 m (30 ft) long truss specimen is constructed using self-consolidated concrete to investigate the constructability and structural capacity of the proposed design. A finite element analysis of the specimen is conducted to investigate stresses at truss diagonals, verticals, and connections. Testing results indicate the production and structural efficiency of the developed system.